Monovalent mRNA XBB.1.5 vaccine effectiveness against COVID-19 hospitalization in Quebec, Canada: Impact of variant replacement and waning protection during 10-month follow-up - Sara Carazo; Danuta M. Skowronski; Nicholas Brousseau; Charles-Antoine Guay; Chantal Sauvageau; Étienne Racine; Denis Talbot; Iulia Gabriela Ionescu; Judith Fafard; Rodica Gilca; Jonathan Phimmasone; Philippe De Wals; et al. (PLoS ONE, 2025)
Background Vaccine formulations targeting contemporaneous subvariants have been developed to respond to SARS-CoV-2 virus evolution. Updated monovalent COVID-19 vaccines targeting the Omicron XBB.1.5 variant (XBB-vaccines) were administered in the province of Quebec, Canada, during 2023 autumn and 2024 spring vaccination campaigns. Our objective was to evaluate mRNA XBB-vaccine effectiveness (VE) against COVID-19 hospitalizations among adults aged ≥60 years overall during a ten-month follow-up period, by subvariant predominant period, and by time since vaccination. Methods We conducted a test-negative case-control study using Quebec population-based administrative data. Specimens collected from individuals aged ≥60 years tested at an acute-care hospital from October 2023 to August 2024 were considered test-positive cases if hospitalized for COVID-19, or controls if test-negative for SARS-CoV-2. Vaccination was defined by receipt of at least one mRNA XBB-vaccine (autumn or spring) dose. Subvariant predominant periods were defined according to whole-genome sequencing data from provincial laboratories: XBB or EG.5 and subvariants (XBB period), BA.2.86, JN.1 or subvariants (JN period), and KP.2 or KP.3 and subvariants (KP period). Multivariable logistic regression analyses estimated VE relative to several comparator groups, primarily those last-vaccinated in 2022, by subvariant period, by time since XBB-vaccination and by number of XBB-vaccine doses (KP period). Results Participants overall and by XBB, JN and KP periods included: 5532 (4.9%) test-positive cases (1321, 1838 and 1372, respectively) and 108473 (95.1%) test-negative controls (12881, 53414 and 28595, respectively); 14584 specimens were collected during periods of subvariant cocirculation. By subvariant period, 3322 (25.8%), 27041 (50.6%) and 15401 (53.9%) controls, respectively, were considered XBB-vaccinated. Overall VE was 30% (95%CI:24–35) and by XBB, JN or KP period: 54% (95%CI:46–62), 23% (95%CI:13–32) and 0% (95%CI:-18–15), respectively. During each subvariant period, the hospitalization risk was reduced only during the first four months post-vaccination. Conclusions Among individuals aged 60 years or older, mRNA XBB-vaccination provided meaningful, albeit limited to first four months post-vaccination, protection against COVID-19 hospitalization due to XBB, JN and KP subvariants. Better vaccines are needed to effectively protect older adults against COVID-19 hospitalizations.